Cross-linking method of sodium hyaluronate gel for injection
By adopting a dual crosslinking process and specific crosslinking agent in sodium hyaluronate gel, the problems of poor crosslinking stability, low biocompatibility, poor injection effect and short maintenance time in the prior art are solved, and a more stable crosslinking structure and better biocompatibility are achieved.
Patent Information
- Application Number
- CN202510047710.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The existing sodium hyaluronate gel has poor cross-linking stability, low biocompatibility, poor injection effect and short maintenance time.
The dual crosslinking process is adopted, first performing the primary crosslinking under alkaline conditions, and then performing the secondary crosslinking under acidic conditions. Polypropylene glycol diglycidyl ether or polyethylene glycol diacrylate is used as the crosslinking agent to form a crosslinking system with EDC.
It significantly improves the degree of cross-linking of sodium hyaluronate, enhances its mechanical strength, stability and biocompatibility, and improves injection effect and maintenance time.
Smart Images

Figure CN119838057A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical cosmetic materials, and in particular to a cross-linking method of sodium hyaluronate gel for injection. Background Art
[0002] The domestic medical beauty industry has gone through the embryonic stage, exploration stage, growth stage and mature stage, and is currently in a stage of gradual standardized development with the help of the Internet era. Among them, gels used in medical beauty surgery are relatively common medical beauty materials. Currently, commonly used gels include a variety of materials, such as silicone rubber, polytetrafluoroethylene and other implantable filling materials, as well as collagen and hyaluronic acid and other injectable filling materials.
[0003] The linear molecular chain of sodium hyaluronate contains multiple hydroxyl groups and multiple carboxyl groups, which can be cross-linked by selecting suitable cross-linking agents such as glutaraldehyde, epoxy ether, carbodiimide, etc. When the amount of cross-linking agent used is small, the cross-linking density is insufficient, and the prepared cross-linked sodium hyaluronate gel has a short existence period in the body; and when the amount of cross-linking agent used is large, although the three-dimensional network structure formed is very tight, which prolongs the degradation time in the body, the prepared cross-linked sodium hyaluronate gel has a hard texture and poor swelling ability, which reduces its injectability. At the same time, after the cross-linking of sodium hyaluronate is completed, some unreacted (including: unbonded at one end and unbonded at both ends) cross-linking agents may remain and be coated in the three-dimensional network structure, affecting its biocompatibility and causing rejection reaction to the human body.
[0004] The commonly used crosslinking agent is 1,4-butanediol diglycidyl ether (BDDE), which can crosslink with sodium hyaluronate well. However, the design specification of BDDE in the finished product is that it cannot be regenerated, and the presence of free BDDE may bring potential hazards, especially for injectable gel materials. Any BDDE molecules that have not crosslinked with sodium hyaluronate or reacted with water in the reaction may have toxic risks. At the same time, the amount of BDDE added also has a certain impact on the double crosslinking.
[0005] Therefore, the related technologies regarding the cross-linking method of sodium hyaluronate gel in the prior art still need to be further improved. Summary of the invention
[0006] In view of this, the present invention proposes a cross-linking method for injectable sodium hyaluronate gel, which solves the technical problems existing in the prior art, such as poor cross-linking stability, low biocompatibility, poor injection effect and short maintenance time.
[0007] The technical solution of the present invention is achieved in this way:
[0008] In one aspect, the present invention provides a method for cross-linking a sodium hyaluronate gel for injection, comprising the following steps:
[0009] S1. Evenly dispersing two sodium hyaluronate dry powders with different molecular weights in an alkaline solution to obtain a sodium hyaluronate alkaline solution;
[0010] S2, adding a crosslinking agent and a phase transfer catalyst to the sodium hyaluronate alkaline solution in step S1, mixing and stirring for 15-30 minutes, and reacting at 40-45° C. for 2-3 hours to obtain a mixture;
[0011] S3, adding a secondary crosslinking agent to the mixture in step S2, and then adding dilute acid to adjust the pH, reacting at 20-25° C. for 2-3 days, filtering, washing, and drying to obtain a powdered solid, which is collected and sieved;
[0012] S4, adding water for injection, swelling under high pressure, collecting the swollen particles, and obtaining the sodium hyaluronate gel for injection.
[0013] On the basis of this technical solution, further preferably, the cross-linking agent in step S2 is polypropylene glycol diglycidyl ether or polyethylene glycol diacrylate.
[0014] On the basis of this technical solution, it is further preferred that the phase transfer catalyst in step S2 includes one of benzyltrimethylammonium hydroxide, benzyltriethylammonium chloride, tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium hydrogen sulfate, trioctylmethylammonium chloride, dodecyltrimethylammonium chloride, and tetradecyltrimethylammonium chloride.
[0015] On the basis of this technical solution, it is further preferred that the mass ratio of the sodium hyaluronate dry powder, the cross-linking agent and the phase transfer catalyst is 1:(4.2-6):(1-3).
[0016] On the basis of this technical solution, further preferably, the molecular weight of the sodium hyaluronate dry powder is 200,000-900,000 Da and 1,000,000-3,000,000 Da respectively.
[0017] On the basis of this technical solution, it is further preferred that the pH of the alkaline solution is 10-14, and it is prepared from 0.4-0.5M sodium hydroxide solution and acetone, and the volume ratio of the sodium hydroxide solution to acetone is 3 / 7-2 / 3.
[0018] On the basis of this technical solution, it is further preferred that the secondary cross-linking agent in step S3 is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC).
[0019] On the basis of this technical solution, more preferably, the mass ratio of the secondary cross-linking agent to the mixture is (0.4-1.7):1.
[0020] On the basis of this technical solution, it is further preferred that the dilute acid in step S3 includes dilute hydrochloric acid, acetic acid or citric acid, and the pH is adjusted to 2-4.5.
[0021] On the basis of this technical solution, it is further preferred that the high pressure in step S4 is 300-303 kPa.
[0022] The cross-linking method of sodium hyaluronate gel for injection provided by the present invention has the following beneficial effects compared with the prior art:
[0023] The cross-linking degree of traditional sodium hyaluronate fillers is unstable, which may lead to inconsistent filling effects and a short maintenance time; the existing BDDE needs to be strictly controlled in dosage when used as a cross-linking agent, and the residual BDDE molecules may be harmful to the human body; therefore, the present invention uses polypropylene glycol diglycidyl ether or polyethylene glycol diacrylate to replace BDDE, and forms a cross-linking system with EDC, accurately controls the dosage of the cross-linking agent and strict cross-linking reaction conditions, so that a more stable cross-linking structure is formed between sodium hyaluronate molecules, thereby improving the stability of the filler in the dermis and ensuring a long-lasting and uniform filling effect;
[0024] In addition, a double cross-linking process is used, firstly performing the primary cross-linking under alkaline conditions, and then performing the secondary cross-linking under acidic conditions. This double cross-linking process can significantly improve the cross-linking degree of sodium hyaluronate, and enhance its mechanical strength, stability and biocompatibility; among them, the alkaline cross-linking with a pH of 10-14 can form a relatively tight cross-linking network, and improve the strength and stability of the gel; the acidic cross-linking with a pH of 2-4.5 can further modify the cross-linking structure, and increase its biological activity and adaptability.
[0025] The final method also includes post-processing to remove impurities, improve product purity and safety, and ensure that the product meets the standards of medical cosmetology; and by precisely controlling reaction conditions and parameters, products with different properties can be produced to meet personalized needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 This is a particle size distribution diagram of the sodium hyaluronate gel for injection prepared in Example 1 of the present invention;
[0028] Figure 2This is a particle distribution diagram of the sodium hyaluronate gel for injection prepared in Example 2 of the present invention under a microscope;
[0029] Figure 3 This is a test chart of the injection pushing force of the sodium hyaluronate gel for injection prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The present invention provides a cross-linking method for sodium hyaluronate gel for injection, wherein a sodium hydroxide solution, acetone and sodium hyaluronate dry powder are mixed in a specific ratio to form a sodium hyaluronate acetone alkaline solution. This unique mixed solution provides a suitable chemical environment for the subsequent cross-linking reaction, helps to promote the cross-linking reaction, and also improves the selectivity and efficiency of the reaction; compared with the traditional single solvent system, the mixed solution can better disperse sodium hyaluronate, so that it is fully in contact with the cross-linking agent and the catalyst, thereby improving the cross-linking effect.
[0032] Example 1
[0033] A cross-linking method for sodium hyaluronate gel for injection comprises the following steps:
[0034] S1. Evenly dispersing 0.2 g of sodium hyaluronate dry powder with a molecular weight of 900,000 Da and 0.5 g of sodium hyaluronate dry powder with a molecular weight of 3,000,000 Da in an alkaline solution to obtain a sodium hyaluronate alkaline solution;
[0035] Specifically, the alkaline solution has a pH of 13 and is prepared from 90 mL of 0.5 M sodium hydroxide solution and 210 mL of acetone.
[0036] S2, adding polypropylene glycol diglycidyl ether and a phase transfer catalyst to the sodium hyaluronate alkaline solution in step S1, mixing and stirring for 15 minutes, and reacting at 45° C. for 2 hours to obtain a mixture;
[0037] Specifically, the phase transfer catalyst in step S2 is benzyltrimethylammonium hydroxide; the mass ratio of the sodium hyaluronate powder, the cross-linking agent and the phase transfer catalyst is 1:4.2:1.
[0038] Polypropylene glycol diglycidyl ether and EDC are selected as cross-linking agents, which have efficient cross-linking ability and can react with sodium hyaluronate molecules under relatively mild conditions to form a stable cross-linking structure;
[0039] In addition, the introduction of quaternary ammonium salt phase transfer catalyst can promote the transfer of crosslinking agents between different phases, improve the reaction rate and crosslinking uniformity. Compared with traditional catalysts, it has higher catalytic activity and selectivity, can effectively reduce reaction temperature and time, and improve production efficiency.
[0040] S3, adding a secondary crosslinking agent to the mixture in step S2, and then adding dilute acid to adjust the pH, reacting at 25° C. for 2 days, filtering, washing, and drying to obtain a powdered solid, which is collected and sieved;
[0041] Specifically, the secondary cross-linking agent in step S3 is EDC, and the mass ratio of the secondary cross-linking agent EDC to the mixture is 0.4:1. The dilute acid in step S3 is dilute hydrochloric acid, and the pH is adjusted to 2. In the acidic environment at this time, acidic cross-linking can further modify the cross-linking structure, which can not only significantly improve the cross-linking degree of sodium hyaluronate, but also enhance its mechanical strength, stability and biocompatibility.
[0042] S4, adding water for injection, swelling under a high pressure of 303 kPa, collecting the swollen particles, and obtaining the sodium hyaluronate gel for injection.
[0043] result: Figure 1 This is the particle size distribution diagram of the sodium hyaluronate gel for injection prepared in Example 1. It can be seen that after double cross-linking of polypropylene glycol diglycidyl ether and EDC, the hydrogel has a uniform three-dimensional structure, the pore sizes are similar, and the compatibility is good.
[0044] Example 2
[0045] A cross-linking method for sodium hyaluronate gel for injection comprises the following steps:
[0046] S1. Evenly dispersing 0.5 g of sodium hyaluronate dry powder with a molecular weight of 200,000 Da and 0.8 g of sodium hyaluronate dry powder with a molecular weight of 3,000,000 Da in an alkaline solution to obtain a sodium hyaluronate alkaline solution;
[0047] Specifically, the alkaline solution has a pH of 13 and is prepared from 120 mL of 0.4 M sodium hydroxide solution and 180 mL of acetone.
[0048] S2, adding polypropylene glycol diglycidyl ether and a phase transfer catalyst to the sodium hyaluronate alkaline solution in step S1, mixing and stirring for 30 minutes, and reacting at 40° C. for 3 hours to obtain a mixture;
[0049] Specifically, in step S2, the phase transfer catalyst is benzyltriethylammonium chloride; the mass ratio of the sodium hyaluronate powder, the cross-linking agent and the phase transfer catalyst is 1:6:3;
[0050] Polypropylene glycol diglycidyl ether and EDC are selected as cross-linking agents, which have efficient cross-linking ability and can react with sodium hyaluronate molecules under relatively mild conditions to form a stable cross-linking structure;
[0051] In addition, the introduction of quaternary ammonium salt phase transfer catalyst can promote the transfer of crosslinking agents between different phases, improve the reaction rate and crosslinking uniformity. Compared with traditional catalysts, it has higher catalytic activity and selectivity, can effectively reduce reaction temperature and time, and improve production efficiency.
[0052] S3, adding a secondary crosslinking agent to the mixture in step S2, and then adding dilute acid to adjust the pH, reacting at 20° C. for 3 days, filtering, washing, and drying to obtain a powdered solid, which is collected and sieved;
[0053] Specifically, the secondary cross-linking agent in step S3 is EDC, and the mass ratio of the secondary cross-linking agent EDC to the mixture is 1.7:1. The dilute acid in step S3 is dilute hydrochloric acid, and the pH is adjusted to 4.5. In the acidic environment at this time, acidic cross-linking can further modify the cross-linking structure, which can not only significantly improve the cross-linking degree of sodium hyaluronate, but also enhance its mechanical strength, stability and biocompatibility.
[0054] S4, adding water for injection, swelling under a high pressure of 303 kPa, collecting the swollen particles, and obtaining the sodium hyaluronate gel for injection.
[0055] result: Figure 2 This is the particle distribution diagram of the sodium hyaluronate gel for injection prepared in Example 2 under a microscope. It can be seen that the particle size distribution of the sodium hyaluronate gel is relatively narrow.
[0056] Example 3
[0057] A cross-linking method for sodium hyaluronate gel for injection comprises the following steps:
[0058] S1. Evenly dispersing 0.3 g of sodium hyaluronate dry powder with a molecular weight of 900,000 Da and 0.7 g of sodium hyaluronate dry powder with a molecular weight of 3,000,000 Da in an alkaline solution to obtain a sodium hyaluronate alkaline solution;
[0059] Specifically, the alkaline solution has a pH of 13 and is prepared from 120 mL of 0.4 M sodium hydroxide solution and 180 mL of acetone.
[0060] S2, adding polypropylene glycol diglycidyl ether and a phase transfer catalyst to the sodium hyaluronate alkaline solution in step S1, mixing and stirring for 20 minutes, and reacting at 42° C. for 2.5 hours to obtain a mixture;
[0061] Specifically, in step S2, the phase transfer catalyst is tetrabutylammonium chloride; the mass ratio of the sodium hyaluronate powder, the cross-linking agent and the phase transfer catalyst is 1:4.5:2;
[0062] Polypropylene glycol diglycidyl ether and EDC are selected as cross-linking agents, which have efficient cross-linking ability and can react with sodium hyaluronate molecules under relatively mild conditions to form a stable cross-linking structure;
[0063] In addition, the introduction of quaternary ammonium salt phase transfer catalyst can promote the transfer of crosslinking agents between different phases, improve the reaction rate and crosslinking uniformity. Compared with traditional catalysts, it has higher catalytic activity and selectivity, can effectively reduce reaction temperature and time, and improve production efficiency.
[0064] S3, adding a secondary crosslinking agent to the mixture in step S2, and then adding dilute acid to adjust the pH, reacting at 22° C. for 2 days, filtering, washing, and drying to obtain a powdered solid, which is collected and sieved;
[0065] Specifically, the secondary cross-linking agent in step S3 is EDC, and the mass ratio of the secondary cross-linking agent to the mixture is 0.8:1. The dilute acid in step S3 is citric acid, and the pH is adjusted to 4. In the acidic environment at this time, acidic cross-linking can further modify the cross-linking structure, which can not only significantly improve the cross-linking degree of sodium hyaluronate, but also enhance its mechanical strength, stability and biocompatibility.
[0066] S4, adding water for injection, swelling under a high pressure of 302 kPa, collecting the swollen particles, and obtaining the sodium hyaluronate gel for injection.
[0067] Example 4
[0068] A cross-linking method for sodium hyaluronate gel for injection comprises the following steps:
[0069] S1. Evenly dispersing 0.2 g of sodium hyaluronate dry powder with a molecular weight of 900,000 Da and 0.8 g of sodium hyaluronate dry powder with a molecular weight of 3,000,000 Da in an alkaline solution to obtain a sodium hyaluronate alkaline solution;
[0070] Specifically, the alkaline solution has a pH of 13 and is prepared from 90 mL of 0.5 M sodium hydroxide solution and 210 mL of acetone.
[0071] S2, adding polyethylene glycol diacrylate and a phase transfer catalyst to the sodium hyaluronate alkaline solution in step S1, mixing and stirring for 20 minutes, and reacting at 45° C. for 2 hours to obtain a mixture;
[0072] Specifically, in step S2, the phase transfer catalyst is benzyltrimethylammonium hydroxide; the mass ratio of the sodium hyaluronate powder, the cross-linking agent and the phase transfer catalyst is 1:4.4:1.5;
[0073] Polyethylene glycol diacrylate and EDC were selected as cross-linking agents, which have efficient cross-linking ability and can react with sodium hyaluronate molecules under relatively mild conditions to form a stable cross-linking structure;
[0074] In addition, the introduction of quaternary ammonium salt phase transfer catalyst can promote the transfer of crosslinking agents between different phases, improve the reaction rate and crosslinking uniformity. Compared with traditional catalysts, it has higher catalytic activity and selectivity, can effectively reduce reaction temperature and time, and improve production efficiency.
[0075] S3, adding a secondary crosslinking agent to the mixture in step S2, and then adding dilute acid to adjust the pH, reacting at 25° C. for 2 days, filtering, washing, and drying to obtain a powdered solid, which is collected and sieved;
[0076] Specifically, the secondary cross-linking agent in step S3 is EDC, and the mass ratio of the secondary cross-linking agent to the mixture is 0.5:1. The dilute acid in step S3 is citric acid, and the pH is adjusted to 3. In the acidic environment at this time, acidic cross-linking can further modify the cross-linking structure, which can not only significantly improve the cross-linking degree of sodium hyaluronate, but also enhance its mechanical strength, stability and biocompatibility.
[0077] S4, adding water for injection, swelling under a high pressure of 303 kPa, collecting the swollen particles, and obtaining the sodium hyaluronate gel for injection.
[0078] Comparative Example 1
[0079] A cross-linking method for injectable sodium hyaluronate gel, which is different from Example 1 in that the cross-linking agent is BDDE.
[0080] Comparative Example 2
[0081] A cross-linking method for sodium hyaluronate gel for injection, which is different from Example 1 in that the cross-linking agent is 1,4-butanediol diglycidyl ether.
[0082] Comparative Example 3
[0083] A cross-linking method for injectable sodium hyaluronate gel, which differs from Example 1 in that no secondary cross-linking agent is added.
[0084] Comparative Example 4
[0085] A cross-linking method for sodium hyaluronate gel for injection, which is different from Example 1 in that the pH of the alkaline solution in step S1 is 9, and the pH of step S3 is 5.
[0086] Comparative Example 5
[0087] A cross-linking method for sodium hyaluronate gel for injection, which is different from Example 1 in that the mass ratio of the sodium hyaluronate dry powder, the cross-linking agent and the phase transfer catalyst is 1:0.8:1.
[0088] Quality Testing
[0089] The sodium hyaluronate gel obtained in each example and comparative example was tested for maintenance effect, adverse reactions and biocompatibility.
[0090] Maintenance effect and adverse reactions: 1 g of the sodium hyaluronate gel prepared in the present invention was mixed into 100 mL of stock solution, and 9 adult healthy mice weighing about 3 kg were selected as test subjects. After anesthesia, 1 mL of the stock solution was injected into the abdomen and the mice were raised normally. The condition of the mice within 72 hours after injection and the condition of the injection site were tested.
[0091] Table 1 Characterization test of medical aesthetic materials
[0092] project Effect duration / month Mouse situation Example 1 13 No adverse reactions Example 2 13 No adverse reactions Example 3 12 No adverse reactions Example 4 12 No adverse reactions Comparative Example 1 11 No adverse reactions Comparative Example 2 10 Slight swelling Comparative Example 3 10 swelling Comparative Example 4 10 swelling Comparative Example 5 11 Slight swelling
[0093] As can be seen from Table 1, the comparison of the results of Example 1 with those of Comparative Examples 1-5 shows that different cross-linking agents, namely the cross-linking system of BDDE and EDC, or no secondary cross-linking, the pH environment during cross-linking, and the excessive ratio of sodium hyaluronate dry powder and cross-linking agent, all have different degrees of influence on the maintenance effect and adverse reactions of the finally prepared sodium hyaluronate gel. The reason may be that there is no suitable acidic environment to modify the cross-linking structure for secondary cross-linking, and the cross-linking degree, mechanical strength, stability and biocompatibility of sodium hyaluronate are all reduced to varying degrees; while polypropylene glycol diglycidyl ether and EDC as cross-linking agents have efficient cross-linking ability, and can react with sodium hyaluronate molecules under relatively mild conditions to form a stable cross-linked structure. Compared with the existing BDDE, there may be free BDDE molecules that react with water, which have certain toxicity to the test mice and induce adverse reactions.
[0094] The injection smoothness test includes the following steps:
[0095] 1. Sample installation
[0096] Fix the syringe on the fixture, ensure that the plunger head of the syringe is tightly connected to the push injection device, and the needle seat of the syringe is partially closed (a suitable plug can be used) to prevent leakage. Connect the pressure sensor to the appropriate position of the push injection device so that the sensor can accurately measure the pressure during push injection.
[0097] 2. Set the injection parameters
[0098] Set the injection speed through the control interface of the injection device. You can refer to the actual clinical injection scenario, for example, set it to a commonly used injection speed, such as 30mm / min. At the same time, ensure that the data acquisition system starts recording data and set a suitable data recording interval, such as recording the pressure value every 0.1s.
[0099] 3. Perform a bolus test
[0100] Start the push device and start pushing at the set speed. During the push process, the data acquisition system will record the pressure changes measured by the pressure sensor in real time. Continue pushing until most of the sample in the syringe is pushed out, or the preset push volume is reached, while observing and recording the pressure change curve.
[0101] 4. Repeat the test
[0102] In order to ensure the accuracy and reliability of the data, the same batch of samples is tested repeatedly (for example, 3-5 times). Before each test, make sure that the syringe is refilled and the system is restored to its initial state. After each test, check whether the equipment and samples are normal. If there are any abnormalities (such as sample leakage, equipment failure, etc.), the test data will be invalid and need to be retested.
[0103] result: Figure 3 This is a pushing force test of the sodium hyaluronate gel prepared in Example 1 of the present invention. It can be seen that the pushing force is small and the injection is uniform, indicating that the gel prepared after the double cross-linking process has good compatibility.
[0104] In summary, the present invention provides a cross-linking method for a sodium hyaluronate gel for injection, wherein polypropylene glycol diglycidyl ether or polyethylene glycol diacrylate is selected to replace BDDE, and together with EDC, a cross-linking system is formed, and then a double cross-linking process is combined, firstly a primary cross-linking is performed under alkaline conditions, and then a secondary cross-linking is performed under acidic conditions. This double cross-linking process can significantly improve the cross-linking degree of sodium hyaluronate, enhance its mechanical strength, stability and biocompatibility, and solve the technical problems of poor cross-linking stability, low biocompatibility, poor injection effect and short maintenance time existing in the prior art.
[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A cross-linking method for sodium hyaluronate gel for injection, characterized in that: The following steps are involved: S1. Evenly dispersing two sodium hyaluronate dry powders with different molecular weights in an alkaline solution to obtain a sodium hyaluronate alkaline solution; S2, adding a crosslinking agent and a phase transfer catalyst to the sodium hyaluronate alkaline solution in step S1, mixing and stirring for 15-30 minutes, and reacting at 40-45° C. for 2-3 hours to obtain a mixture; S3, adding a secondary crosslinking agent to the mixture in step S2, and then adding dilute acid to adjust the pH, reacting at 20-25° C. for 2-3 days under acidic conditions, filtering, washing, and drying to obtain a powdered solid, which is collected and sieved; S4, adding water for injection, swelling under high pressure, collecting the swollen particles, and obtaining the sodium hyaluronate gel for injection.
2. The cross-linking method of sodium hyaluronate gel for injection according to claim 1, characterized in that: The cross-linking agent in step S2 is polypropylene glycol diglycidyl ether or polyethylene glycol diacrylate.
3. The cross-linking method of sodium hyaluronate gel for injection according to claim 2, characterized in that: The phase transfer catalyst in step S2 is one of benzyltrimethylammonium hydroxide, benzyltriethylammonium chloride, tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium hydrogen sulfate, trioctylmethylammonium chloride, dodecyltrimethylammonium chloride and tetradecyltrimethylammonium chloride.
4. The cross-linking method of sodium hyaluronate gel for injection according to claim 3, characterized in that: The mass ratio of the sodium hyaluronate dry powder, the cross-linking agent and the phase transfer catalyst is 1:(4.2-6):(1-3).
5. The cross-linking method of sodium hyaluronate gel for injection according to claim 1, characterized in that: The molecular weights of the sodium hyaluronate dry powder are 200,000-900,000 Da and 1,000,000-3,000,000 Da respectively.
6. The cross-linking method of sodium hyaluronate gel for injection according to claim 1, characterized in that: The alkaline solution has a pH of 10-14 and is prepared from 0.4-0.5M sodium hydroxide solution and acetone, wherein the volume ratio of the sodium hydroxide solution to the acetone is 3 / 7-2 / 3.
7. The cross-linking method of sodium hyaluronate gel for injection according to claim 1, characterized in that: The secondary cross-linking agent in step S3 is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide.
8. The cross-linking method of sodium hyaluronate gel for injection according to claim 7, characterized in that: The mass ratio of the secondary cross-linking agent to the mixture is (0.4-1.7):
1.
9. The cross-linking method of sodium hyaluronate gel for injection according to claim 1, characterized in that: The dilute acid in step S3 is one of dilute hydrochloric acid, acetic acid and citric acid, and the pH is adjusted to 2-4.
5.
10. The cross-linking method of sodium hyaluronate gel for injection according to claim 1, characterized in that: The high pressure in step S4 is 300-303 kPa.
Citation Information
Patent Citations
Degradable scaffold medical film preparation method
CN105396181A
Heterogeneous catalysis bi-crosslinked sodium hyaluronate gel and preparation method thereof
CN107043468A
Enzymolysis-resistant crosslinked sodium hyaluronate gel, and preparation method and preparations thereof
CN108250462A
Hyaluronic acid derivatives for cell delivery carriers and their process for preparing the same
KR1020080062092A
Method for producing double-crosslinked hyaluronate material
US20040127698A1